“Cultivating a Sense of Duty and Responsibility to Society”: the Specificity of the “Service-Learning” Approach in China - A. D. Galkina; V. S. Nikolskiy (Высшее образование в России, 2024)
Civic education and youth nurturing continue to be the focus of academic discussions. Over the past decade, in Russian higher education there has been an increasing interest in intensification of youth policy, as well as the introduction of new ideological, philosophic disciplines and modules. In this regard, the experience of those foreign countries that, like Russia, are faced with the tasks of forming national identity, citizenship, solidarity, and preserving traditional values, is worth exploring. The People’s Republic of China is one of the most telling examples among such countries. However, the development of civic education in China has not received sufficient attention in academic publications. This is especially noticeable in the service-learning pedagogical approach.As a result of the study, the influence of the cultural and historical context on civic education in China was revealed. Additionally, the differences in the implementation of service-learning in various regions of the country were identified. Firstly, China faces the challenges of countering the globalization, formation of the national identity, and preserving the traditional culture. Secondly, the country needs to unite mainland China and special administrative regions (SARs). The study found that civic education in general and service learning in particular are highly dependent on cultural and historical context. The political development of the country, the evolution of its education system, and the socio-economic differentiation between regions of China have a significant impact on the service-learning initiatives.